THE EFFECT OF XYZ GENERATION CHARACTERISTICS TO E-COMMERCE C-TO-C: A REVIEW - Dewanti, Paula; Indrajit, Richardus Eko (Fakultas Teknik Universitas Persada Indonesia YAI, 2018)
Biggest shifts have been in technology for marketplace, E-Commerce model, especially. The world has becomemore global and market is easily accessible. Consumers become very refined in looking for their choice of goodsand services that they are looking for. Today, there are numerous online marketplace options available to suitconsumer needs. E-Commerce offers a wide range of information technology to enhance communications andtransactions with any related stakeholders in an organization. Focusing on XYZ generation characteristic, thisstudy is sampling three of Indonesiaâs leading online marketplace providing consumer-to-consumer approach,one of the business models that bridge one consumer to another for their transaction of products or services.Consumer engagement is one fact that online marketplace focus on. Understanding the consumer to improvecustomer service is bringing online marketplace to the next level, rather than just updating their platform of selling.